Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and cerebral atherosclerotic stenosis: a retrospective study - Yating Han; Yuting Gao; Mengyuan Qiu; Yida Wang; Shenjie Li; Mengmeng Guo; Tao Zheng; Zunjing Liu (Lipids in Health and Disease)
Abstract Background Ischemic stroke (IS) is one of the leading causes of death and disability worldwide. Early identification of dyslipidemia associated with cerebral atherosclerosis is of great importance for reducing the risk of IS. The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a novel lipid biomarker to assess atherosclerosis. The aim of this study is to investigate the association between NHHR and cerebral atherosclerotic stenosis using DSA imaging data, including intracranial/extracranial stenosis, anterior/posterior circulation stenosis, severe stenosis, and symptomatic stenosis. Methods Patients who underwent DSA examination from July 2022 to December 2024 were included. Participants were divided into four groups based on NHHR levels. Univariable and multivariable logistic regression were applied to assess the association between NHHR and cerebral atherosclerotic stenosis, including intracranial and extracranial stenosis, anterior and posterior circulation stenosis, severe stenosis, and symptomatic stenosis. Restricted cubic splines (RCS) were applied to analyze and visualize the association between NHHR and cerebral atherosclerotic stenosis. Results A total of 853 patients were included in the final analysis. After adjusting for covariables, compared to patients in the lower NHHR groups, those in the higher NHHR groups had a significantly higher occurrence rate of extracranial stenosis, posterior circulation stenosis, severe stenosis, and symptomatic stenosis. Multivariable-adjusted RCS showed a nonlinear association between NHHR and posterior circulation stenosis, and a linear positive association between NHHR and symptomatic stenosis. Conclusions NHHR may serve as a lipid management indicator for patients with extracranial stenosis, posterior circulation stenosis, severe stenosis, or symptomatic stenosis. NHHR could be an independent risk factor for symptomatic stenosis, which can aid in risk stratification and treatment decision-making for cerebral atherosclerotic stenosis patients.